The Influence of Teacher Interaction Patterns in Integrated Social Studies Learning on the Learning Interests of Class VIII Students of SMP Negeri 4 Amalatu - Hehanussa, Nur Saada; Tetelepta, Edward Gland; Manakane, Susan Evelin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
For a teacher, finding the ideal engagement pattern takes work. Every student is unique, and they all have different beliefs and perspectives. The teacher interaction pattern depends on the material delivered; the teacher said that one, one, two, or three interaction patterns can be used in Learning. This study calculates the percentage of results using quantitative methods. Used to calculate the percentage of numbers from a survey that examines the impact of teacher engagement styles during geography teaching on students' enthusiasm for Learning. In addition, the study results showed that the interaction pattern of teachers of class VIII students of SMP Negeri 4 in integrated social studies Learning impacts their learning motivation. Proven by the calculation results obtained by the value Given F (Deviation from linearity) of 2.691 and a sig value of 0.175 ± 0.05, it can be concluded that there is a significant linear relationship in the teacher interaction pattern with students' learning interests. It can be concluded that the learning interests of class VIII students of SMP Negeri 4 Amalatu are influenced by the way teachers interact with them during integrated social studies learning. There is a significant influence; this is done using the t-test, producing a sig.0.000 value of 0.05 and a Tcount value of 4.606 Table 2.093. Then, it can be seen from the calculation of the coefficient of determination that the variable of teacher interaction patterns (x) in influencing student learning interest (y) is 52.8%, with 47.2% influenced by factors not included in this analysis.